2013
DOI: 10.1021/ma401314x
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Polymer Synthesis via Catalyst-Transfer Polycondensation (CTP): Mechanism, Scope, and Applications

Abstract: The recent discovery of a living, controlled chain-growth method for synthesizing π-conjugated polymers has ignited the field and led to the development of many new materials. This Perspective focuses on the mechanistic underpinnings of the synthetic transformation, highlighting the controversial hypotheses and supporting data. A critical analysis of the literature revealed that the monomer scope remains largely limited to electron-rich monomers at this time. Last, a brief overview of some exciting new materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
164
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(166 citation statements)
references
References 150 publications
1
164
0
Order By: Relevance
“…We designed and synthesized gemini thiophene monomers in which 2-bromo-5-iodo-thiophenes, which are able to be processed by CTP, [17][18][19] are tethered by alkylene straps (Scheme 1b: GMm, where GM stands for 'gemini monomer' and m represents the strap length). These monomers were synthesized in seven steps, as shown in Scheme 1c.…”
Section: Synthesis Of Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…We designed and synthesized gemini thiophene monomers in which 2-bromo-5-iodo-thiophenes, which are able to be processed by CTP, [17][18][19] are tethered by alkylene straps (Scheme 1b: GMm, where GM stands for 'gemini monomer' and m represents the strap length). These monomers were synthesized in seven steps, as shown in Scheme 1c.…”
Section: Synthesis Of Monomersmentioning
confidence: 99%
“…13,14 The structural parameters regarding P3XT include regioregularity (head-to-tail selectivity), molecular weight and polydispersity, which are currently controllable because of recent advances in nickel catalyst-transfer polycondensation (CTP). [15][16][17][18][19][20] In this study, we focus our attention on another structural parameter, specifically the dihedral angle of the conjugated backbone, because it governs the effective conjugation length along the polymer chain. 21,22 Indeed, the dihedral angle has an important role in device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The original Grignard metathesis polymerization scheme, reported by McCullough, suggested that following reductive elimination, the growing polymer associates nondiffusively with the Ni catalyst. It is now recognized that the mechanism proceeds instead via a Ni-polymer π-complex, [23][24][25] The Ni catalyst does not, however remain associated with a single chain end, as substantial evidence exists to support a chain walking process, allowing for bidirectional propagation during CTP. 26,27 Motivated by these reports (as well as those suggesting Ni 0 diffusion and catalyst resting states), 23,28 and inspired by our understanding of the ATRP mechanism, we consider periods of deactivation and subsequent reactivation within the GRIM polymerization mechanism.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…6 In fact, we have recently succeeded in the synthesis of diblock copolymers (poly-2) consisting of unsheathed P3HT and sheathed polythiophene. Although the CTP method is expected to yield such unprecedented polymer structures, the monomer scope still remains limited in terms of both electronic and steric effects, 7 and we have not yet succeeded in the synthesis of other IMWs such as poly-3 through the CTP method.Poly-3 was synthesized through Yamamoto polymerization, 5 and in this regard, one report from the Scherf group 8 has attracted our interest. They synthesized block copolymers of poly[2,7-(9,9-dialkyl)fluorene] and poly(2,6-(4,4-dialkyl)-4H-cyclopenta[2,1-b:3,4-b¤]dithiophene) using Yamamoto polymerization conditions despite the fact that the propagation proceeds through the step-growth mechanism (Scheme 2).…”
mentioning
confidence: 99%
“…6 In fact, we have recently succeeded in the synthesis of diblock copolymers (poly-2) consisting of unsheathed P3HT and sheathed polythiophene. 4 Although the CTP method is expected to yield such unprecedented polymer structures, the monomer scope still remains limited in terms of both electronic and steric effects, 7 and we have not yet succeeded in the synthesis of other IMWs such as poly-3 through the CTP method.…”
mentioning
confidence: 99%